'Closure' at Manus Island and carceral expansion in the open air prison. Issue 7 (2nd October 2020) - Giannacopoulos, Maria; Loughnan, Claire
ABSTRACT: Manus prison was officially closed in 2017 following Papua New Guinea's (PNG) Supreme Court decision that the existence of the camp breached the PNG Constitution. The 'Namah' decision was significant in signalling and seeking to curb the imperial reach of Australian law but insufficient in resolving the question of refugee imprisonment. Far from ending the imprisonment of refugees, the closure following the judicial ruling has facilitated the expansion of the imperial carcerality that has characterized Australia's immigration detention policy since 1992. By revealing how refugee incarceration has been extended and offshore processing instantiated following the closure of Woomera camp in 2003, we argue that official closures of refugee camps Woomera and Manus have been constitutive of carceral expansion that is imperial in form and that reiterates patterns of colonial violence. After tracking imperial expansion, we make a call for prison abolition in the refugee incarceration arena as this is a critical decolonizing strategy.